Annual plant reviews, Volume 23: Biology of the plant cuticle - Riederer, Markus (Blackwell, 2012)
Detailing the developments in the field, this book is directed at researchers and professionals in plant biochemistry, plant physiology, plant ecology, phytopathology and environmental microbiology, in both the academic and industrial sectors.